Effect of traditional plants in Sri Lanka on skin fibroblast cell number - Sano, Katsura (Data Brief, 2018)
This article describes the effects of extracts of several plants collected in Sri Lanka on the cell number of human skin fibroblasts. This study especially focuses on the plants traditionally used in indigenous systems of medicine in Sri Lanka, such as Ayurveda, as described below (English name, “local name in Sri Lanka,” scientific name). Bougainvillea plant, “bouganvilla,” Bougainvillea grabla (Nature׳s Beauty Creations Ltd., 2014) [1], purple fruited pea eggplant,”welthibbatu,” Solanum trilobatum (Nature׳s Beauty Creations Ltd., 2014) [2], country borage plant, “kapparawalliya,” Plectranthus amboinicus (Nature׳s Beauty Creations Ltd., 2014) [3], malabar nut plant, “adhatoda,” Justicia adhatoda (Nature׳s Beauty Creations Ltd., 2014) [4], long pepper plant,”thippili,” Piper longum (Nature׳s Beauty Creations Ltd., 2014) [5], holy basil plant, “maduruthala,” Ocimum tenuiflorum (Nature׳s Beauty Creations Ltd., 2014) [6], air plant, “akkapana,” Kalanchoe pinnata (Nature׳s Beauty Creations Ltd., 2014) [7], plumed cockscomb plant, “kiri-henda,” Celosia argentea (Nature׳s Beauty Creations Ltd., 2014) [8], neem plant,”kohomba,” Azadirachta indica (Nature׳s Beauty Creations Ltd., 2014) [9], emblic myrobalan plant, “nelli,” Phyllanthus emblica (Nature׳s Beauty Creations Ltd., 2014) [10]. Human skin fibroblast cells were treated with various concentration of plant extracts (0–3.0%), and the cell viability of cells were detected using calcein assay. The cell viabillity profiles are provided as line graphs.